Respuesta :

Answer: [tex]-\frac{1}{2}[/tex]

=========================================================

Work Shown:

Apply the quotient rule

[tex]h(x) = \frac{g(x)}{1+f(x)}\\\\h(x) = \frac{A}{B}\\\\h'(x) = \frac{A'*B-A*B'}{B^2}\\\\h'(x) = \frac{g'(x)*(1+f(x))-g(x)*(1+f(x))'}{(1+f(x))^2}\\\\h'(x) = \frac{g'(x)*(1+f(x))-g(x)*f'(x)}{(1+f(x))^2}\\\\h'(2) = \frac{g'(2)*(1+f(2))-g(2)*f'(2)}{(1+f(2))^2}\\\\h'(2) = \frac{5*(1-3)-4*(-2)}{(1-3)^2}\\\\h'(2) = \frac{-2}{4}\\\\h'(2) = -\frac{1}{2}\\\\[/tex]

ACCESS MORE